THE GENERALIZED CONSTRUCTION OF PSEUDONONDETERMINISTIC HASHING - Luzhetsky, Volodymyr; Baryshev, Yuriy (International Journal of Computing, 2014)
This article is devoted to the development of hash constructions, which are based on the pseudonondeterministic hash conception. The conception allows to design hash functions with improved infeasibility to cryptanalysis. Both proposed constructions and known ones are generalized as pseudonondeterministic constructions.